ОСОБЛИВОСТІ МОДЕЛЮВАННЯ ВІБРАЦІЙНИХ ПРОЦЕСІВ РУХОМИХ ВУЗЛІВ ЕЛЕКТРОЕНЕРГЕТИЧНОГО ОБЛАДНАННЯ З МЕТОЮ ЇХНЬОГО ЗАСТОСУВАННЯ У СИСТЕМАХ ТЕХНІЧНОГО ВІБРОДІАГНОСТУВАННЯ - Гижко, Ю.І.; Мислович, М.В.; Остапчук, Л.Б.; Сисак, Р.М. (Інститут електродинаміки НАН України, Київ, 2014)
The paper analyzed the main peculiarities of vibration processes arising during the operation of moving parts of power electrical equipment. Based on the analysis, authors proposed to use the class of linear periodic stochastic processes to elaborate the mathematical model of those vibrations. Following that approach authors developed new mathematical model of the vibrations which takes into account both the periodicity of the process and the impact of vibration sources of different physical nature and different localization. The model allows analytical investigation of probabilistic characteristics of vibrations in the moving parts of the power electrical equipment, the substantiation of most informative diagnostic parameters for detection and classification of defined failures of those parts, construction of the efficient decision rules for their diagnostics. References 5, figure 1.